Similar Aquaporin9 and MAPK Expression Profiles in the Liver of Types 1 and 2 Diabetes Mellitus - Hou, Jiaojiao; Li, Yuan; Ren, Xüxia; Gao, Fei; Chen, Yuqin; Yi, Yaoxing; Kang, Lili; Luo, Yürui; Yang, Mei (Hormone and Metabolic Research, 2018)
Aquaporin-9 (AQP9) is an aquaglyceroporin that biophysically conducts water, glycerol, and other small solutes. AQP9 is expressed in hepatocytes on the sinusoidal surfaces of hepatocyte plates in the liver, where it is considered responsible for the glycerol uptake in gluconeogenesis. However, limited information is available on the expression and regulating mechanism of AQP9 in different hyperglycemia models. Thus, this study examined the expression patterns of AQP9 and mitogen-activated protein kinase (MAPK) in Types 1 and 2 diabetes mellitus (DM) to clarify the roles and regulating mechanism of AQP9 in gluconeogenesis. Compared with the control group, the AQP9 expression significantly increased in both Types 1 and 2 DM, and the increased expression was associated with the activation of phosphorylated JNK (p-JNK) and the inhibition of phosphorylated p38 (p-p38). By contrast, phosphorylated ERK remained stable in the liver with Type 1 or 2 DM. These effects could be reversed by insulin treatment. That is, insulin downregulated AQP9 by inhibiting p-JNK and activating p-p38. The upregulation of AQP9 could be involved in gluconeogenesis and co-regulated by the JNK and p38 MAPK pathway in both Types 1 and 2 DM.
Keywords: aquaporin; MAPK; diabetes mellitus